2020
DOI: 10.1038/s41598-020-64215-w
|View full text |Cite
|
Sign up to set email alerts
|

SVF-derived extracellular vesicles carry characteristic miRNAs in lipedema

Abstract: Lipedema is a chronic, progressive disease of adipose tissue with lack of consistent diagnostic criteria. The aim of this study was a thorough comparative characterization of extracellular microRNAs (miRNAs) from the stromal vascular fraction (SVF) of healthy and lipedema adipose tissue. For this, we analyzed 187 extracellular miRNAs in concentrated conditioned medium (cCM) and specifically in small extracellular vesicles (sEVs) enriched thereof by size exclusion chromatography. No significant difference in me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 68 publications
(65 reference statements)
0
26
0
2
Order By: Relevance
“…Normalized delta Cq-values (dCq) were used for clustering analysis based on Euclidean distance and complete linkage. Unit variance row scaling was applied for hierarchical clustering and principal component analysis (PCA) [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Normalized delta Cq-values (dCq) were used for clustering analysis based on Euclidean distance and complete linkage. Unit variance row scaling was applied for hierarchical clustering and principal component analysis (PCA) [ 30 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…This fact has popularized the use of SEC amongst its competitors for blood-based exosome-associated biomarker discovery research [52], [58]. SEC has been used successfully to isolate, purify and enrich exosomes from a variety of biological fluids including plasma [68]- [73], serum [74]- [76], bovine and human milk [77], [78], urine [79]- [82], saliva [83], [84], tears [83], cerebrospinal fluid [85], [86], synovial fluid [87], nasal lavage [89], seminal fluid [88] and stromal vascular fraction (SVF) from adipose tissue [63], [64] (Table 3). Recent findings reported at the ISEV Virtual Conference 2020 suggest SEC is superior to other techniques in isolation of pure exosomes from human body fluids (unpublished findings).…”
Section: Ideal Methods For Exosome Isolation: Secmentioning
confidence: 99%
“…SEC coupled techniques are specifically useful within the context of adipose tissue-derived exosomes [61], [63], [64]. Flaherty et al [64] reported that standard isolation techniques are inefficient for extraction of exosomes from adipocytes given their high lipid content (which could affect vesicle density).…”
Section: Application Of Sec For Isolation Of Exosomes From Adipose Timentioning
confidence: 99%
See 2 more Smart Citations